High transparency La2O3-CaO-B2O3-SiO2 glass for diagnosis x-rays shielding material application. (July 2019) - Kaewjaeng, S.; Kothan, S.; Chaiphaksa, W.; Chanthima, N.; Rajaramakrishna, R.; Kim, H.J.; Kaewkhao, J.
Abstract: The La2 O3 added in (80-x) B2 O3 :10SiO2 :10 CaO:xLa2 O3 glass (where x = 10, 15, 20, 25 and 30 mol%) were prepared by melt-quenching technique have been investigated for x-ray shielding, physical and optical properties. The density of the glass samples found to increase which increasing La2 O3 concentrations. The transmission spectra result demonstrated that the glass samples had high transparency similar with commercial window, corresponding to high visibility in the visible region as already observed. The mass attenuation coefficient (µm ) were increased with the decreasing of kilovoltage peak (kVp) of an x-ray instrument, and increased with the increasing of La2 O3 concentration. The half value layer (HVL) and ten value layer (TVL) of glass samples trend to decrease when the kVp of an x-ray instrument decrease and La2 O3 concentrations increase. The trend of lead equivalent increase which Ln2 O3 concentrations and the kVp of an x-ray instrument increasing. All results indicating the potential of the prepared glasses as Pb-free and high visibility for diagnostic x-ray shielding material. Highlights: La2 O3 based glass were prepared. Density of the glass increased with La2 O3 . High transparency and visibility similar with commercial window. Shielding properties increased with La2 O3 . Prepared glasses as Pb-free and high visibility for diagnostic x-ray shielding material.